2023
DOI: 10.1093/cercor/bhad171
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive volumetric phenotyping of the neonatal brain in Down syndrome

Abstract: Down syndrome (DS) is the most common genetic cause of intellectual disability with a wide range of neurodevelopmental outcomes. To date, there have been very few in vivo neuroimaging studies of the neonatal brain in DS. In this study we used a cross-sectional sample of 493 preterm- to term-born control neonates from the developing Human Connectome Project to perform normative modeling of regional brain tissue volumes from 32 to 46 weeks postmenstrual age, accounting for sex and age variables. Deviation from t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 92 publications
(133 reference statements)
1
3
0
Order By: Relevance
“…The biological interpretation of these enlargements, whether they are developmental or compensatory, is not clear due to the diverse range of functions associated with these regions. Overall, our mouse findings further underscore the relevance and validity of the Dp1Tyb model as it recapitulates some neuroanatomical alterations observed in humans with DS ( Fukami-Gartner et al, 2023 ).…”
Section: Discussionsupporting
confidence: 69%
See 2 more Smart Citations
“…The biological interpretation of these enlargements, whether they are developmental or compensatory, is not clear due to the diverse range of functions associated with these regions. Overall, our mouse findings further underscore the relevance and validity of the Dp1Tyb model as it recapitulates some neuroanatomical alterations observed in humans with DS ( Fukami-Gartner et al, 2023 ).…”
Section: Discussionsupporting
confidence: 69%
“…These observed changes in the Dp1Tyb model resemble the heterogeneous findings from humans with DS. For instance, studies in humans have also highlighted the significance of decreased prefrontal cortex and hippocampal volume as key neuroanatomical correlates of cognitive deficits in this population ( Fukami-Gartner et al, 2023 ; McCann et al, 2021 ; Pinter et al, 2001 ; Teipel et al, 2004 ). On the other hand, reports of slight enlargements of deep grey matter structures are reminiscent of our findings of increased subcortical volumes ( Raz et al, 1995 ; White et al, 2003 ; Wilson et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In DS, temporal lobe volume is greatly reduced compared to neurotypical individuals ( Takashima et al, 1994 ; Pinter et al, 2001 ; Guidi et al, 2008 ), with MRI studies reporting a ~30% volume reduction in the hippocampus (HPC), the primary structure supporting declarative recognition and spatial memory functions ( Barker and Warburton, 2011 ). Morphological alterations of the HPC are already present in DS fetuses, persist through adulthood and are exacerbated with age ( Takashima et al, 1994 ; Guidi et al, 2008 ; Fukami-Gartner et al, 2023 ).…”
Section: Introductionmentioning
confidence: 99%
“…To this end, magnetic resonance imaging (MRI) studies have shown decreases in the overall brain volume in people with DS compared to neurotypical people, with several brain regions particularly affected, such as the frontal lobes, the hippocampus, and the cerebellum (Koenig et al, 2021;McCann et al, 2021). On the other hand, the complexity of this syndrome is also reflected in some posterior cortical and subcortical regions that are relatively preserved or even increased in volume (Fukami-Gartner et al, 2023;Pinter et al, 2001). Regarding cellular and molecular changes, increases in glial markers (such as inositol and glutamine) and decreases in neuronal markers (such as glutamate) have been reported using magnetic resonance spectroscopy (MRS), in both humans and animal models of DS (Lin et al, 2016;Patkee et al, 2021;Shonk and Ross, 1995;Vacca et al, 2019).…”
Section: Introductionmentioning
confidence: 99%